Pro SharePoint 2013 branding and responsive web development - Overfield, Eric; Zhang, Rita; Medina, Oscar; Khipple, Kanwal (Apress Imprint: Apress, 2013)
Pro SharePoint 2013 Branding and Responsive Web Development is the definitive reference on the technologies, tools, and techniques needed for building responsive websites and applications with SharePoint 2013.  The book focuses on solutions that provide the best browser experience for the myriad of devices, browsers, and screen orientations and resolutions. Web technology has changed considerably in the past few years. Microsoft has embraced the new generation of open standards represented by HTML5 and JavaScript, and these changes are represented in a fundamental shift in how SharePoint 2013 supports web content management and publishing. Authors Eric Overfield, Oscar Medina, Kanwal Khipple, and Rita Zhang join forces to dive into the new features and capabilities provided by SharePoint 2013 and combine them with the latest techniques in responsive web design and development to demonstrate how to build modern and progressive websites and applications.  Pro SharePoint 2013 Branding and Responsive Web Development covers the following technologies: SharePoint 2013 Server Edition Office 365 SharePoint Online Expression Blend 2013 Napa Tools for Office and SharePoint Development Visual Studio 2012 HTML5 and CSS3 JavaScript, JQuery, JQuery UI, Modernizr, and the Bootstrap Framework SharePoint 2013 Client Object Model